2019
DOI: 10.3390/jcm8070939
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α/TNF-R System May Represent a Crucial Mediator of Proliferative Synovitis in Hemophilia A

Abstract: Hemophilic arthropathy (HA) typically begins with proliferative synovitis that shares some similarities with inflammatory arthritides, in which the proinflammatory cytokine tumor necrosis factor (TNF)-α has a crucial pathogenetic role. Inappropriate release of TNF-α was shown to contribute to arthropathy development following intra-articular bleeding in hemophilic mice. Here, we were interested in determining whether systemic levels of TNF-α and synovial tissue expression of the TNF-α/TNF receptor (TNF-R) syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 42 publications
(79 reference statements)
0
9
0
Order By: Relevance
“…Following LPS activation of FLS in RA, non‐expression of TNF‐α has been reported due to epigenetic regulation 17 . Of note is that TNF‐α is likewise key to inflammation in HA, as recently published with regard to the role of the iRhom2/ADAM17/TNF‐α pathway 39 and also as a crucial mediator of proliferative synovitis in haemophilia A 39 …”
Section: Discussionmentioning
confidence: 96%
“…Following LPS activation of FLS in RA, non‐expression of TNF‐α has been reported due to epigenetic regulation 17 . Of note is that TNF‐α is likewise key to inflammation in HA, as recently published with regard to the role of the iRhom2/ADAM17/TNF‐α pathway 39 and also as a crucial mediator of proliferative synovitis in haemophilia A 39 …”
Section: Discussionmentioning
confidence: 96%
“…Consequently, TNF antagonists, e.g., etanercept, are clinically efficacious for the treatment of RA as they delay joint destruction via several mechanisms, such as decreasing cell recruitment to the inflamed joint [34,35] and synovial chemotactic cytokine expression [36]. In a recent study, Maneti M et al reported the crucial role of TNF-α/TNF-R system in the pathogenesis of hemophilic athropathy, therefore can be employed as a new attractive target for the prevention and treatment of joint damage in hemophilic arthropathy patients [37], which was proven by the current study.…”
Section: Discussionmentioning
confidence: 99%
“…52 In another study, serum levels of the proinflammatory cytokine TNF-α were significantly elevated in patients with hemophilic arthropathy compared to healthy controls (p<0.0001). 84 Moreover, TNF-α levels were positively correlated with the number of joint bleeds, degree of synovial hypertrophy, and clinical and ultrasound joint outcomes. The authors suggest that TNF-α is involved in the progression of hemophilic arthropathy and could be a suitable biomarker to detect joint deterioration in patients with hemophilia.…”
Section: Biomarkers and Bone Health In Patients With Hemophiliamentioning
confidence: 95%
“…The authors suggest that TNF-α is involved in the progression of hemophilic arthropathy and could be a suitable biomarker to detect joint deterioration in patients with hemophilia. 84 However, TNF-α is an acute phase inflammatory marker that is elevated in a range of conditions, including rheumatoid arthritis, and as such is not specific to hemophilic submit your manuscript | www.dovepress.com…”
Section: Biomarkers and Bone Health In Patients With Hemophiliamentioning
confidence: 99%